1999
DOI: 10.1046/j.1523-1747.1999.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Expression of Fas (CD95) Ligand in Metastatic Melanoma Revealed by Longitudinal Analysis

Abstract: The expression of Fas ligand has recently been proposed as a novel tumor escape mechanism for melanoma. To establish the characteristics of Fas ligand expression during the course of melanoma progression we performed a longitudinal study analyzing primary tumors as well as subsequently evolving metastases. In primary melanoma Fas ligand was expressed in two of 20 lesions; this expression was weak and restricted to few parts of the tumors. The Fas ligand positive primary melanomas were rather thick, i.e., 8.5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

2001
2001
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 19 publications
2
34
0
1
Order By: Relevance
“…The major finding of our study was that Fas expression in melanoma cells correlated significantly with the frequency of apoptosis of melanoma cells and that apoptosis of melanoma cells affected the prognosis of melanoma patients. We also found that both melanoma cells and infiltrating lymphocytes can express Fas and FasL in clinical specimens, extending the earlier findings that Fas is expressed in infiltrating lymphocytes (21) and FasL is expressed in melanoma cells (21)(22)(23)(24), though the lymphocyte apoptosis in itself was not significantly related to the prognosis. Therefore, these results indicate that the melanoma cell apoptosis mediated by the Fas-FasL system may affect the growth of melanoma and the prognosis of melanoma patients.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The major finding of our study was that Fas expression in melanoma cells correlated significantly with the frequency of apoptosis of melanoma cells and that apoptosis of melanoma cells affected the prognosis of melanoma patients. We also found that both melanoma cells and infiltrating lymphocytes can express Fas and FasL in clinical specimens, extending the earlier findings that Fas is expressed in infiltrating lymphocytes (21) and FasL is expressed in melanoma cells (21)(22)(23)(24), though the lymphocyte apoptosis in itself was not significantly related to the prognosis. Therefore, these results indicate that the melanoma cell apoptosis mediated by the Fas-FasL system may affect the growth of melanoma and the prognosis of melanoma patients.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, investigation of apoptosis of Faspositive lymphocytes induced by FasL-expressing tumor cells has been focused on tumor escape from immunological rejection in various malignant neoplasms, including hepatocellular carcinoma (7), colon cancer (18,35), and melanoma (21,23,24). Hahne (21) reported that FasL-expressing melanoma cells and Fas-positive lymphocytes were found in metastatic melanoma lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fas expression at the cell surface is observed in cell lines derived from a variety of tumors, including glioma, colon carcinoma, breast carcinoma, prostate cancer, neuroblastoma, melanoma and medulloblastoma. [24][25][26][27][28][29][30] Immunohistochemical studies have confirmed that such expression can be observed in tumors in vivo, or on freshly isolated tumor cells ex vivo. Cytotoxic drugs and tumor cell p53 status are known to have an influence on Fas-mediated apoptosis.…”
Section: Cancer Fas and Trailmentioning
confidence: 99%